2020
DOI: 10.1111/jcmm.14872
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock transcription factor 1 regulates exercise‐induced myocardial angiogenesis after pressure overload via HIF‐1α/VEGF pathway

Abstract: Exercise training is believed to have a positive effect on cardiac hypertrophy after hypertension. However, its mechanism is still not fully understood. Herein, our findings suggest that heat shock transcription factor 1 (HSF1) improves exercise-initiated myocardial angiogenesis after pressure overload. A sustained narrowing of the diagonal aorta (TAC) and moderately-intense exercise training protocol were imposed on HSF1 heterozygote (KO) and their littermate wild-type (WT) male mice. After two months, the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Several studies showed that HIF is activated under hypoxic conditions of different heart diseases such as ischemic heart disease or heart failure [ 81 ]. Morand et al demonstrated that chronic exposure to hypoxia induces ischemic ventricular arrhythmias and unexpected cardiac death [ 82 ].…”
Section: Dual Role Of Hypoxia In Acute and Chronic Disease Conditimentioning
confidence: 99%
“…Several studies showed that HIF is activated under hypoxic conditions of different heart diseases such as ischemic heart disease or heart failure [ 81 ]. Morand et al demonstrated that chronic exposure to hypoxia induces ischemic ventricular arrhythmias and unexpected cardiac death [ 82 ].…”
Section: Dual Role Of Hypoxia In Acute and Chronic Disease Conditimentioning
confidence: 99%
“…Exercise-induced cardioprotection is underpinned by various molecular mechanisms, such as activation of heat shock and ER stress proteins as well as cyclooxygenase, enhancing the antioxidant capacity and autophagy processes [ 32 ]. Several studies investigated cardiac and skeletal muscle performance using mild to severe TAC with or without exercise in mice [ 8 , 18 ]. Studies on TAC and exercise intervention always applied exercise as secondary intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of exercise on HF development and associated muscle remodeling using the TAC model in mice was studied by Wang et al and Tian et al [ 8 , 18 ]. They observed improved cardiac performance following exercise training with increased intensity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports, it was found that HIF-1 α was an upstream signal factor for VEGF, and HIF-1 α could induce the VEGF expression [ 22 , 34 , 35 ]. However, in this clinical study, we did not find this relationship.…”
Section: Discussionmentioning
confidence: 99%